The Game of Dice on People's Entertainment Performance Islamic Perspective (Study in The District Juwana, Central Java) - Kuswardani Kuswardani; Ricky Alan Mutadho; Marisa Kurnianingsih; Andria Luhur Precocious (Faculty of Law, Universitas Pekalongan, 2023)
Introduction: Gambling is an act that has a speculative element, without which is there is no hard work. Purposes of the Research: The research aims are to describe dice game as a form of gambling from an Islamic perspective, moreover, to explain why Indonesian prohibits gambling. Methods of the Research: This manuscript is library research and empirical as an example to explain gambling as a habit in the community. Results / Findings / Novelty of the Research: The research results point out that firstly The Islamic prohibit gambling chance in the conventional forms (like this dice game) or online gambling. And Islam also forbids gambling has become a habit. second, the prohibition is as in the Word of God Al Baqarah/2:219, Al Maidah /5 90 – 91, and Hadith of the Prophet Muhammad SAW which was narrated by Imam Bukhari and Muslim. Thirdly, the Penal Code defines gambling as a crime, however, the gamble is without permission. The novelty of the research is ambiguous in the formulated with the consideration of Law Number 7 of 1974 on Controlling Gambling.